2012
DOI: 10.1103/physreve.85.051912
|View full text |Cite
|
Sign up to set email alerts
|

Phase lag in epidemics on a network of cities

Abstract: We study the synchronization and phase lag of fluctuations in the number of infected individuals in a network of cities between which individuals commute. The frequency and amplitude of these oscillations is known to be very well captured by the van Kampen system-size expansion, and we use this approximation to compute the complex coherence function that describes their correlation. We find that, if the infection rate differs from city to city and the coupling between them is not too strong, these oscillations… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 28 publications
1
26
1
Order By: Relevance
“…When analysing a large geographical area made of several interacting communities, synchronization and persistence have been often considered in association because asynchrony was considered a possible reinfection mechanism between neighbouring areas after local fadeouts. Several works have shown that synchronization between spatially distributed communities depends on the strength of their coupling as well as the intensity of the external seasonality [3][4][5][6][7][8][9]. Ruxton [3] explored the synchronization and persistence in weakly coupled non-seasonal chaotic systems and found that they did not fully synchronize, thus permitting re-colonization of local patches after extinction occurred.…”
Section: Introductionmentioning
confidence: 99%
“…When analysing a large geographical area made of several interacting communities, synchronization and persistence have been often considered in association because asynchrony was considered a possible reinfection mechanism between neighbouring areas after local fadeouts. Several works have shown that synchronization between spatially distributed communities depends on the strength of their coupling as well as the intensity of the external seasonality [3][4][5][6][7][8][9]. Ruxton [3] explored the synchronization and persistence in weakly coupled non-seasonal chaotic systems and found that they did not fully synchronize, thus permitting re-colonization of local patches after extinction occurred.…”
Section: Introductionmentioning
confidence: 99%
“…Our model is clearly related to meta-population models, that have been considered previously as models of infection spread in aggregated populations (Lloyd and May, 1996;Riley and others, 2003;Rozhnova et al, 2012). The novelty in our work is that we consider a different population level limit -metapopulations often are considered as a small number of large clumps (for example representing cities in a country), where as we consider a large number of small clumps (more reminiscent of households within a country).…”
Section: Discussionmentioning
confidence: 99%
“…The general procedure to do this is reviewed in Ref. [27] and has been previously applied to models of epidemics on networks [28,29], albeit in situations where the nodes of the network contained many individuals, rather than just one, as in the present context.…”
Section: Formulation Of the Modelmentioning
confidence: 99%